3D Printing of Shape Memory Polymers for Flexible Electronic Devices. Issue 22 (24th September 2015) - Zarek, Matt; Layani, Michael; Cooperstein, Ido; Sachyani, Ela; Cohn, Daniel; Magdassi, Shlomo
Abstract : The formation of 3D objects composed of shape memory polymers for flexible electronics is described. Layer‐by‐layer photopolymerization of methacrylated semicrystalline molten macromonomers by a 3D digital light processing printer enables rapid fabrication of complex objects and imparts shape memory functionality for electrical circuits.